THE CATHAL SYNDROME HÜYÜK: OBSERVATIONS ON EARLY AGGLOMERANTS TRENDS - Makowski Hanula, Krzysztof (2000)
The author approaches the problematic that is presented when interrogating us on the emergence of the urbanism in the Andean area. He has made a theoretical revision of the models applied in that zone, which have been based on che paradigms of evolucionist court of Gordon Childe and Julian Steward, researchers that worked in che patterns of establishments of Mesopotamia, Greece, ltaly and medieval Europe. The "Syndrome of Catal Hüyük" refers to the scientific tradition of explaining the Andean urbanism making a parallel with the development phases discovered in that establishment of the Middle East. The author proposes the assumption of own models of analysis and obtain of this way, an appropriate understanding of the first Andean complex societies that have been characterized mainly by a pattern of «antiurban» establishment. This doesn't mean to ignore the evolucionist proposals, but to assimilate the important propositions and to apply them to our reality.